2018
DOI: 10.33899/rden.2020.126450.1012
|View full text |Cite
|
Sign up to set email alerts
|

Compressive Strength of Type IV Dental Stone With Ag Nanoparticles

Abstract: The aim of the current study is to investigate the effect of different concentrations of Ag nanoparticles on the compressive strength of type IV dental stone. Materials and Methods: Total specimens of this research are 66 specimens, it is divided into 3 groups, the first group is for wet strength , second group is for dry strength and third group is for scanning electron microscope analysis. 0.2%, 0.5% ,1.0% ,1.5% and 2.0% weight of Ag NPs incorporated into type IV dental stone then evaluated both wet and dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…It was found that as the concentration of ZnO nanoparticles was increased, the CS value decreased. A similar study done by Salah et al [17] using Ag nanoparticles as a reinforcing material had findings that were in similarity to our study.…”
Section: Discussionsupporting
confidence: 93%
“…It was found that as the concentration of ZnO nanoparticles was increased, the CS value decreased. A similar study done by Salah et al [17] using Ag nanoparticles as a reinforcing material had findings that were in similarity to our study.…”
Section: Discussionsupporting
confidence: 93%
“…Salah et al reported similar results regarding the addition of silver nanoparticles to dental stone type 4. In their study, the addition of silver nanoparticles did not show any effect on the morphology of dental stone compared to the control without nanoparticles [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…The specimens were crushed into fragments by the continually growing compressive force, at which point digitalized values in Newton/mm2 (MPa) were recorded. Compressive strength values for each sample were calculated [15].…”
Section: Test Measurement For Compressive Strengthmentioning
confidence: 99%